Banking of Management: Implementation and Evaluation (Study Literature Review) - Mohamad Yusuf Kurniawan; Christophorus Indra Wahyu Putra; Kamsariaty Kamsariaty; Abi Prasidi; Agus Setiawan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The purpose of this literature review is to develop hypotheses regarding the influence between variables that can be used for further research in the field of risk management. The article on the influence of risk identification and risk assessment on the effectiveness of risk management mediated by risk mitigation capabilities is a scientific literature article in the field of risk management. The approach used in this literature review is descriptive qualitative. The data collection technique used is literature study or review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. In previous studies, one relevant previous article was used for each independent variable. The results of the literature review are as follows: 1) Net profit is related to banking management; 2) Total liabilities are related to banking management; and 3) Total assets are related to banking management.